2014
DOI: 10.4314/njt.v33i4.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Suitability of Low-Density Polyethylene (LDPE) Waste as Fine Aggregate in Concrete

Abstract: ABSTRACT ABSTRACTThis study evaluates an alternative solid waste management option for Low This study evaluates an alternative solid waste management option for Low This study evaluates an alternative solid waste management option for Low This study evaluates an alternative solid waste management option for Low commonly called "pure water sachet" as partial replacement of sand in concrete. Three mix ratios of 1:1:2, 1:1.5:3, commonly called "pure water sachet" as partial replacement of sand in concrete. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Utilization of wastes from polyethylene terephthalate to modify conventional Bituminous Asphaltic Concrete (BAC) will help remove post-consumer plastic wastes from the waste stream and likewise help enhance the properties of ordinary BAC [11]. In terms of bulk density, pulverized Low-Density Polyethylene plastic waste obtained from "pure water" sachet wastes could be reasonably classified as ultralightweight fine aggregate [1].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of wastes from polyethylene terephthalate to modify conventional Bituminous Asphaltic Concrete (BAC) will help remove post-consumer plastic wastes from the waste stream and likewise help enhance the properties of ordinary BAC [11]. In terms of bulk density, pulverized Low-Density Polyethylene plastic waste obtained from "pure water" sachet wastes could be reasonably classified as ultralightweight fine aggregate [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Worldwide, plastic products contribute substantially to an ever increasing volume of municipal solid waste (MSW) streams. Globally, it constitutes 7-9% of MSW and 2% in Lagos State, Nigeria [1]. As a result of rapid industrial growth in various fields together with population growth, an obvious increase in waste generation rates for various types of waste materials is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Dharmaraj and Iyappan [9] used low density polyethylene (LDPE), for partial replacement of fine aggregate that was grinded (or) shredded (or) pulverized, with specific gravity reported at 0.89, while that of fine aggregate was indicated at 2.7. Soboji and Owamah [8] indicated specific gravity of 0.92 for LDPE. According to Adejumo and Jibrin [13], waste plastics obtained from old/discarded waste plastic tanks in Maitumbi, Nigeria, indicated specific gravity of 2.22, while sand was reported at 2.63.…”
Section: Plastic/ Plastic Waste Properties Applicability and Effectmentioning
confidence: 99%
“…According to Chunchu and Putta [7], recycled high impact polystyrene could replace up to 30 per cent of natural river sand (by volume) for production of eco-friendly durable and flowable concrete. According to Soboji and Owamah [8], low density polyethylene (LDPE) plastic waste recycling in concrete is environmentally friendly and it should be encouraged. The concept of plastic waste mixing in concrete could be a very environmentally-friendly method of solid waste disposal in landfills as indicated by Dharmaraj and Iyappan [9].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation by [19] revealed that the reinforcement benefit increases with an increase in waste plastic strip content and length and that the maximum CBR value of a reinforced system is approximately three (3) times that of an unreinforced system. The paper [24] evaluated the suitability of low density polyethylene (LDPE) waste as fine aggregate in concrete. From his findings LDPE plastic concrete could be used in production of non-load bearing structural members such as tiles and partitions.…”
mentioning
confidence: 99%